HUBUNGAN ANTARA POLA ASUH ORANG TUA DENGAN PERKEMBANGAN MENTAL ANAK PADA PROSES TUMBUH KEMBANG DI SD BENTAKAN 1 SUKOHARJO - Dinar Ariasti; Tunjung Sri Yulianti; Ana Pratiwi (KOSALA : Jurnal Ilmu Kesehatan, 2013)
Background. one part of child development is mental development. Mentaldevelopment is the increasing ability to think, feel, do various situations everydaylife as well as increased ability to see ourselves and others. Mental developmentof a child is influenced by internal factor and eksternal factor. Internal factorinclude genetic and hormonal influenced. While external factor include nutrition,environment and affection both the family and the people around him. Fromobservations of public researches tend to not pay attention to the relationshipbetween parenting and development mental. People tend not to care about theparenting that they impose on their child. From the initial study showed that fourpeople not to care about the proper upbringing for their children.The purpose of this study was to determine the relationship of parenting andmental development of children in the growth process in SD Bentakan ISukoharjo.Subjects were children from first and second class under the age of 6-7 years inSD Bentakan I Sukoharjo. Sampling is done with saturated sampling technique,namely by taking all members of the population being sampled because thepopulation is small.Methods in this study is a correlation study, case-control approach. Data wereobtained by questionnaire and observation method to observe parenting methodand mental development in children aged 6-7 years. The data have beencollected and analyzed with the chi square test with p = 0.05.The results of the study there were parenting parents most widely applied is ademocratic parenting style that is 23 parents (57,5 %), whereas parenting is theleast permissive parenting as many as 4 parents (10%). After being tested byChi-Square SPSS version 16.0 with Î± = 5% (0.05) of 0000 thus obtained p valueof p <0.05, which means that Ho is rejected and Ha accepted.The conclusion of this study is that there is a relationship betweenparentingand mental development of children in the growth process in SDBentakan I Sukoharjo.Keyword : parenting, mental development